Hofmeister effect in the Keggin-type polyoxotungstate series. Issue 1 (6th October 2020) - Yao, Sa; Falaise, Clément; Ivanov, Anton A.; Leclerc, Nathalie; Hohenschutz, Max; Haouas, Mohamed; Landy, David; Shestopalov, Michael A.; Bauduin, Pierre; Cadot, Emmanuel
Abstract : The chaotropic character of Keggin-type polyoxotungstate anions was evaluated with respect to their ability to bind to γ-cyclodextrin (γ-CD) by varying the global charge density of the nanometer-sized polyanion. Abstract : The chaotropic character of Keggin-type polyoxotungstate anions was evaluated with respect to their ability to bind to γ-cyclodextrin (γ-CD) by varying the global charge density of the nanometer-sized polyanion. The strengths of the host–guest association were analyzed within the series of isostructural [XW12 O40 ] n − anions where the ionic charge varies from 6- to 3- depending on the heteroatom, respectively, X = H2 2+, B 3+, Si 4+ or P 5+ . Titration experiments using complementary techniques (ITC, DOSY NMR, and electrochemistry) revealed that the affinity between γ-CD and polyoxometalates (POMs) is directly correlated to the charge density of the Keggin anion as reflected in the values of the binding constants K 1:1 . These constants increase dramatically following the order: [H2 W12 O40 ] 6− < [BW12 O40 ] 5− < [SiW12 O40 ] 4− < [PW12 O40 ] 3− . Additionally, cloud point experiments on a non-ionic surfactant resulted in the same series of POMs, emphasizing the general affinity of these inorganic Keggin-ions to non-ionic organic soft matter due to a general solvent effect arising from the weakening of the hydration sphere with decreasing ionic charge. Furthermore, single crystal X-ray diffraction analysis showed distinct organizations of the POMs with γ-CD in the solid-state, where the moderate chaotrope [BW12 O40 ] 5− interacts with the external wall of the γ-CD, while on the other side of the series, [PW12 O40 ] 3− penetrates deeply into the cavity of the γ-CD through its secondary rim offering optimal contact area. Finally, our investigations revealed the unique behavior of [PW12 O40 ] 3−, which displayed not only the highest affinity of the POMs to γ-CD ( K 1:1 > 10 5 M −1 ), but also the ability to interact with both CD faces resulting in a wide variety of supramolecular aggregates.